Measuring pinch strength before and after haemodialysis session in patients with end stage renal failure - Asif, Mohammad Musa; Javed, Muhammad Asbar (Journal of the Pakistan Medical Association, 2022)
The objective of the study was to observe the change in Pinch Strength (PS) of arteriovenous fistula (AVF) arm and non-AVF arm before and after haemodialysis (HD). A total of 31 patients (21 Male and 10 Female) undergoing HD during January and February 2020 at a trust hospital were selected through purposive sampling. Mean PS was calculated from the measurements taken using the Jamar digital pinch gauge with an interval of five seconds between each measurement. Paired sample T-test was applied using SPSS 20. The mean PS values for AVF arm when compared before and after the session were 3.64 ±1.01 and 2.87 ±1.20 kgs (p<0.01), whereas for non AVF arm PS values were 3.96 ±1.50 and 3.69 ±1.37 kgs (p=0.09). It was concluded that PS of AVF arm decreased more significantly after HD as compared to the non AVF arm. Keywords: Pinch strength, Haemodialysis, arteriovenous fistula, Musculoskeletal. Continuous...